Disparity or discrimination: interaction effects of race, ethnicity, and gender on probation failure in a Midwestern sample - Murphy, Laura D. (Kansas State University, 2018)
At year end 2016 over 3.7 million Americans were under probationary supervision. In response to institutional overcrowding, the U.S. has been increasingly reliant on community corrections. Though there has been extensive research into various aspects of the criminal justice system, the area of community corrections, specifically probation, has seen relatively little scrutiny. Through quantitative analysis of probationary data, this study examined a Midwestern population of closed probationary cases. Through a framework of intersectionality, various intersectional identities are examined for likelihood of failure. Focusing on the prevalence of negative outcomes for not only racial and ethnic minorities, but also intersections of race, ethnicity, and gender. Utilizing logistic regression analysis, each model examines race, ethnicity, and sex against probation failure. After an initial baseline model, intersections of race/ethnicity were run. Using probation success as a control outcome in each of the models. Across all models, race and ethnicity were found to be significantly and positively associated with probation failure. Additionally, standardized coefficients indicate Black and Black/Hispanic categories to represent strong effect on negative probation outcome. Of note, sex though unreliable in numerous models, was found only to be a significant and strong predictor in the model examining Black probationers. Possible explanations, study limitation, future research, and policy implication are offered in the discussion and conclusion section.
Keywords: probation; race; post-racial; colorblind; disparity